Pembinaan dan Pembentukan Ikatan Remaja Masjid Dalam Upaya Memajukan Kualitas Remaja di Kampung Gunung Bakti - Wildan Solihin; Ahmad Fajar (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2023)
Adolescents are a vulnerable age group who are prone to engaging in negative behaviors, such as promiscuity. Therefore, it is necessary to provide guidance and empowerment to adolescents to develop their potential and noble character in accordance with the values of the Qur'an and Sunnah. One of the platforms for providing guidance is through the mosque youth, which focuses on mosque activities, Islamic knowledge, education, youth, and skills. The aim of empowering and establishing the mosque youth is to explore the potential of adolescents to realize noble character according to the Qur'an and Sunnah. Through leadership and organizational training, youth are invited to develop themselves and implement programs that have been designed, such as the Muttaqien Learning House. It is hoped that these programs can improve the quality of learning outside of school and become a platform for personal development and youth interest. The empowerment method used is Participatory Action Research (PAR), which involves adolescents in the decision-making process and implementation of guidance programs. Youth are encouraged to actively participate in leadership and organizational training, as well as designing programs that meet their needs. Through this method, adolescents are expected to become agents of change who are empowered and actively involved in advancing the surrounding environment. The results of the mosque youth empowerment program are the establishment of the Muttaqien Learning House, which improves the quality of learning outside of school. This program is expected to benefit the community, especially students in Gunung Bakti. In addition, mosque youth have also been trained to develop their skills and potential and become leaders who can lead mosque and social activities in the surrounding environment. It is hoped that this guidance and empowerment program for mosque youth will continue and have a significant positive impact on the community. Keywords: Coaching, youth, mosque